Bi-allelic mutations in FASTKD5 are associated with cytochrome c oxidase deficiency and early- to late-onset Leigh syndrome - Antonicka, Hana; Weraarpachai, Woranontee; Szigety, Katherine M.; Kopajtich, Robert; Gibson, James B.; Van Hove, Johan L.K.; Friederich, Marisa W.; Lopriore, Piervito; Neuhofer, Christiane; Van Hove, Roxanne A.; Cole, Michel A.; Reisdorph, Richard; et al. (American journal of human genetics, 2025)
Using exome sequencing, we identified compound heterozygous variants of unknown significance in FASTKD5, a gene that codes for a mitochondrial protein essential for processing mRNAs at non-canonical cleavage sites in the primary mitochondrial transcript, in three subjects with Leigh syndrome, a progressive neurodegenerative disease characterized by lesions in the brainstem and basal ganglia. Among the three subjects, we identified three missense variants and two frameshift variants leading to a premature stop codon. Analysis of fibroblasts from two subjects showed reduced steady-state levels of FASTKD5 protein by immunoblot, reduced translation of the cytochrome c oxidase subunit 1, impaired assembly of complex IV, and a consequent decrease in cytochrome c oxidase enzymatic activity. The extent of these deficiencies appeared to correlate with the severity of the clinical phenotype. Expression of a wild-type FASTKD5 cDNA, but not cDNAs expressing the missense mutations, rescued all the molecular defects in the subjects’ fibroblasts, demonstrating that the alleles are pathogenic. Two of the three identified missense mutations resulted in near complete loss of function, while one was hypomorphic, resulting from impaired protein stability. These cases of mitochondrial disease associated with bi-allelic variants in FASTKD5 add to a growing list of primary genetic mutations causing Leigh syndrome associated with complex IV deficiency. Mutations in FASTKD5, which codes for a protein essential for processing the primary mitochondrial transcript, were identified in subjects who presented with Leigh syndrome and cytochrome c oxidase deficiency. Leigh syndrome is a genetically heterogeneous, progressive neurodegenerative disorder, and these cases add to the growing list of causal genetic defects.